Application of the hypervalent iodine reagent to the synthesis of some pentasubstituted aporphine alkaloids - Ratchanok Pingaew (2018)
The oxidative biaryl coupling of various N-substituted 1- benzyltetrahydroisoquinolines to the corresponding aporphines by the hypervalent iodine reagent was studied. The study sheds light on the unifying mechanism of the reaction illustrating the requirement of the p-p coupling via the six-membered transition state as the initial step. The finding was applied to the synthesis of some pentasubstituted aporphine alkaloids. © Georg Thieme Verlag Stuttgart.